Effects of iba and media on the growth performance of three cultivars of grapes (Vitis Vinifera L.) (Bangladesh Journal of Botany, 2023)
Annual branches of three grape cultivars, namely ‘Xia Hei’ grape, ‘Eastern Star’ grape and ‘Giant Rose’ grape were first treated with Indole-3-butyric acid (IBA) solution, then inserted in different media and then n their growth performances were studied. The growth performance of the three grape cultivars were: ‘Xia Hei’ > ‘Eastern Star’ > ‘Giant Rose’. Media (M4) was the most conducive to improve the survival per cent of gape rooted cuttings. This study provides a reference for choosing a suitable method to grow rooted cuttings taken from grape annual branches, which would furthermore improve the survival rate of young vines.Bangladesh J. Bot. 52(3): 763-774, 2023 (September)